Understanding and fine tuning molecular recognition - Epa, Kanishka Navodh (Kansas State University, 2013)
Co-crystallization allows the manipulation of physical properties of a given compound without affecting its chemical behavior. The ability to predict hydrogen bonding interactions, provides means to the rational design of supramolecular architectures. It also makes it possible to select with a degree of accuracy, a few co-formers that have a high probability of forming co-crystals with a compound of interest, instead of blindly screening against a large number of candidates. To study the effects of changing electronic environment on the ability to form co-crystals, five symmetric dioximes of different hydrogen bond donating ability were synthesized with different functional groups on the carbon α to the oxime moiety. It was shown that the supramolecular yield increase with the positive MEP value on the donor site. In order to further explore this relationship between calculated MEP values and supramolecular selectivity three asymmetric ditopic donors containing phenol carboxylic acid and aldoxime groups were screened against a series of asymmetric ditopic acceptors. Nine crystal structures show that the supramolecular outcome can be predicted according to Etter’s rules by ranking donors and acceptors according to calculated MEP values. To explore the possibility of using the same approach with other hydrogen bond donors, three asymmetric ditopic donor ligands containing cyanooxime groups were synthesized and screened against a series of asymmetric ditopic acceptors. Nine out of ten times the supramolecular outcome could be predicted by MEP calculations 1-deazapurine exists in two tautomeric forms (1H and 3H) in aqueous solution, which have very different hydrogen bonding environments. The 3H tautomer forms a self-complementary dimer involving a donor and an acceptor site leaving a second acceptor site vacant. In order to stabilize this tautomer the molecule was screened against a of series hydrogen and halogen bond donors. Four out of five structures obtained showed 3H tautomer. The 1H tautomer is the geometric complement of urea. Therefore the molecule was screened against a series of N,N-diphenylureas and all five structures showed the 1H tautomer.
Keywords: Molecular recognition; Co-crystal; Hydrogen bond; Cyano-oxime; Chemistry (0485)